Hollow-core PCF for terahertz sensing: A new approach for ethanol and benzene detection - Md. Golam Sadeque; Suchana Aktar Tithi; Md. Safiul Islam; A. H. M. Iftekharul Ferdous; Diponkar Kundu; Md. Galib Hasan; Md. Zakirul Islam Sarker (PLoS ONE, 2025)
Terahertz (THz) spectroscopy is becoming a powerful technique for non-destructive, label-free chemical sensing with applications ranging from medicinal research to security screening. Enhancing THz spectroscopy’s sensitivity and selectivity is crucial to maximizing its potential. In this work, we offer a novel optical fiber design, square shape core PCF that is tailored to exploit improved optical features at exterior in the THz region. This analysis suggests that a square shape and three layers with square air apertures for the cladding and core would be ideal. The mathematical analysis is carried out at THz wave dissemination utilizing FEM and boundaries circumstance of the Perfectly Matched Layer. Using the simulation method, the constructed square PCF sensor achieves very high relative sensitivity (94.45%, 94.80%) at 2 THz for two compounds: ethanol (n = 1.354), and benzene (n = 1.36). On the other hand, the low confinement loss (CL) values for the same two compounds at 2 THz are 1.17 ×  10−05 dB/m, and 1.32 ×  1 0−05 dB/m, in that order. We also looked at the potential applications of this special fiber in a variety of fields, including environmental monitoring, chemical sensing, and biomedical diagnostics. The square PCF with square core has hitherto unexplored opportunities for the development of extremely selective and sensitive THz spectroscopic devices with important social consequences in domain of THz perception of chemicals.